The effectiveness of promotional tools in Bukit Indah Johor / Rofiza Rahman - Rahman, Rofiza (2004)
Bukit Indah Johor is one of developer that had use promotional tools to find and obtain the prospective customer to buy a product and be loyal to them. The promotional tools can gives the best impact in the organization especially for the company that involve in development sector. The purpose of this project is to identify which one of the promotional tools that most capable and effective in promoting houses especially in Bukit Indah Johor to the potential customer. The study is also hopefully would assist in determining how the promotional tools operate in gather the prospective customer to buy a house. The effectiveness of promotional tools like exhibition, show house and brochure will determine the successful of the organizations itself. All the developer companies are depend with this promotional tools in order for the company to compete with other competitor and beside it also illuminates the customer awareness of new product launching in the market. Further more, the housing sector like Bukit Indah Johor need to use this promotional tools because they need to compete with other competitor in the same sector. By making a differences promotional activities can create the potential customer like to make a deal and buy the houses in Bukit Indah Johor.